THE CORRELATION AMONG RETICENCE, PERSONALITY TYPES AND SPEAKING PROFICIENCY OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF PGRI UNIVERSITY PALEMBANG - Indah Pratiwi Hrp; Sofendi Sofendi; Ismail Petrus (University of Kuningan, 2022)
This study aims to investigate the correlations among reticence, personality types and speaking proficiency. For this purpose, the Unwillingness-to-Communicate Scale (UCS) questionnaire and the IPIP Big-five questionnaire were used. Moreover, speaking proficiency test to the sample was employed to find the correlation among students’ reticence, personality types and speaking proficiency. The questionnaire and speaking test result revealed students’ reticence tend to reflect attitudes toward communication, and the students’ dominant personality type was agreeableness, and students’ speaking proficiency was in moderate category. The results revealed that, there was a significant correlation between traits (agreeableness, emotional stability, openness of experience) of personality type and speaking proficiency and there was a significant correlation between personality types and (vocabulary) aspect of speaking proficiency.